Titone, Eos e le cicale: iconologia del repertorio figurativo greco-romano - D'Orlando, Dario (O T I V M, 2024)
Tithonus is a character who is unique within the Trojan cycle. Although he was not involved in the war to defend Ilius, his story is nevertheless deeply connected to his lover, the goddess Eos. His narrative in the ancient world frequently involves the cicada as a symbol of mutual identity. Tithonus and cicadas are closely associated with immortality, old age, and sexuality, and can be read and understood through the study of ancient sources, both literary and iconographic.